Sistem Layanan Pengaduan Berbasis Web pada Kantor Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPMPTSP) di kabupaten Nabire - Arief Rahman Hakim; Natalia Setyaningrum S; Cici Kamalia (Jurnal Teknologi dan Informatika, 2024)
The existence of this public complaint service can help the public in submitting their complaints. Complainants to one-stop integrated service offices often feel disappointed when their complaints are not managed or responded to well, so it is important to manage complaints that can be managed well. Complaints must be planned by the Nabire district One Stop Integrated Services (DPMPTSP) public service provider. Reporters are all parties who submit complaints to the Public Service Complaints Management body, including citizens and residents, whether individuals, groups or legal entities, who are beneficiaries of the services of the Licensing Department. So far, the complaint system is still limited to manual methods and the use of platforms such as WhatsApp. This condition results in various problems, including slow complaint resolution due to limitations in the use of paper or the WhatsApp platform. The risk of human error, such as losing the complaint form, also increases with the use of these manual methods. The WhatsApp application, which is not a dedicated platform for complaints, also has privacy flaws that could threaten user information if not properly encrypted. Apart from that, using Telegram or WhatsApp as a platform for complaints also does not guarantee optimal data security. Messages sent through such applications are vulnerable to thirdparty access if not properly encrypted, increasing privacy risks for users. Therefore, the use of web-based applications can be an appropriate and effective solution for handling complaints. Relevant agencies must allocate resources to develop more sophisticated digital complaint systems.